2000
DOI: 10.1021/jp0018450
|View full text |Cite
|
Sign up to set email alerts
|

Structural Effects on Electrical Conduction of Conjugated Molecules Studied by Scanning Tunneling Microscopy

Abstract: We have studied electrical conduction of conjugated molecules with phenyl rings embedded into alkanethiol self-assembled monolayers (SAMs), to investigate the molecular structural effect on the electrical conduction. Scanning tunneling microscope (STM) images of this surface revealed that the conjugated molecules with phenyl rings adsorbed mainly on defects and domain boundaries of the pre-assembled alkanethiol (nonanethiol C9) SAM and formed conjugated domains. In the case of conjugated molecules with one or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
238
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(248 citation statements)
references
References 45 publications
9
238
0
1
Order By: Relevance
“…Phenyl and phenyleneethynylene-based molecules thiol bridged to Au electrodes have been extensively employed in recent experiments. [5][6][7][8][9][10][11] Theoretical studies of current-voltage ͑I -V͒ characteristics a͒ Electronic mail: yhkim@kias.re.kr b͒ Author to whom correspondence should be addressed. Electronic mail: wag@wag.caltech.edu have been also reported with different methodologies at varying levels of computational complexity.…”
Section: Introductionmentioning
confidence: 99%
“…Phenyl and phenyleneethynylene-based molecules thiol bridged to Au electrodes have been extensively employed in recent experiments. [5][6][7][8][9][10][11] Theoretical studies of current-voltage ͑I -V͒ characteristics a͒ Electronic mail: yhkim@kias.re.kr b͒ Author to whom correspondence should be addressed. Electronic mail: wag@wag.caltech.edu have been also reported with different methodologies at varying levels of computational complexity.…”
Section: Introductionmentioning
confidence: 99%
“…R30º structures; the absence of the methylene spacer makes it more difficult to obtain highlyordered structures. 29 It is possible that the differences in order and packing density could lead to error in the estimation of J 0 . The introduction of a methylene spacer between the phenyl group and the anchoring atom also influences the value of the injection current; that is, the J 0 is higher for SAMs with a methylene spacer than for those without one.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25][26][27][28] (The exception is thiophenol (HSPh) which has been reported to form poorly defined SAMs, possibly due to the weak intermolecular forces between the aromatic rings. 22,24,29 ) The surface structure of thiolates on metal is the same for SAMs of alkanethiolates and SAMs of aromatics ((√3 x √3)R30º on gold and (√7 ×√7)R10.9ºon silver), but the cant angle (α) for the aromatics is slightly less than that of the alkanethiolates (α = ~20º for SAMs of terphenylthiol on Au and α = ~30º for SAMs of alkanethiols on Au). 22,30 Oligophenylene groups present in a SAM adopt a near-planar conformation and pack in a herringbone structure.…”
Section: Introductionmentioning
confidence: 99%
“…STM and C-AFM, in conjunction with methods including use of Hg-drop electrodes, have been used as promising tools for studying the electrical conductance of molecules along the molecular axis [267,268], crossed wires [269], and break junctions [270,271]. As early as the late 90s, the conductance of single molecules embedded in insulating SAM films was discussed and evaluated by Bumm et al [237] and others [272][273][274][275][276], by use of STM. It was, however, shown that estimation of the electrical conductance of adsorbed molecules by use of STM is quite complicated compared with techniques in which the electrode is directly attached to the molecules [267][268][269][270][271].…”
Section: Self Assembled Monolayersmentioning
confidence: 99%